2012
DOI: 10.1128/mcb.00133-12
|View full text |Cite
|
Sign up to set email alerts
|

KDM3B Is the H3K9 Demethylase Involved in Transcriptional Activation of lmo2 in Leukemia

Abstract: f Histone lysine methylation and demethylation are considered critical steps in transcriptional regulation. In this report, we performed chromatin immunoprecipitation with microarray technology (ChIP-chip) analysis to examine the genome-wide occupancy of H3K9-me2 during all-trans-retinoic acid (ATRA)-induced differentiation of HL-60 promyelocytic leukemia cells. Using this approach, we found that KDM3B, which contains a JmjC domain, was downregulated during differentiation through the recruitment of a corepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 31 publications
4
100
0
Order By: Relevance
“…KDM3B was recently characterized as a member of the JumonjiC domain-containing histone demethylases that shows specificity toward H3K9 and is involved gene activation in leukemia cells [25, 26], however, a role for this factor in PEV has not been reported. To test whether increased recruitment of KDM3B by H3K9M nucleosomes might result in decreased H3K9-methylation, we knocked down or over-expressed its Drosophila homolog, JHDM2, in wing imaginal discs.…”
mentioning
confidence: 99%
“…KDM3B was recently characterized as a member of the JumonjiC domain-containing histone demethylases that shows specificity toward H3K9 and is involved gene activation in leukemia cells [25, 26], however, a role for this factor in PEV has not been reported. To test whether increased recruitment of KDM3B by H3K9M nucleosomes might result in decreased H3K9-methylation, we knocked down or over-expressed its Drosophila homolog, JHDM2, in wing imaginal discs.…”
mentioning
confidence: 99%
“…All the JMJD1 family members contain the JMJC domain and are capable of specifically removing H3K9me1 and H3K9me2 methylation modifications but not H3K9me3 (Okada et al, 2007;Kim et al, 2010;Kim et al, 2012). It is now generally accepted that JMJD1C is the third member of the KDM3 family, i.e., KDM3C.…”
Section: Discussionmentioning
confidence: 99%
“…JMJD1C can specifically prevent H3K9me1 and H3K9me2 methylation, and has no catalytic effect on H3K9me3 (Okada et al, 2007;Kim et al, 2010;Kim et al, 2012). Studies have shown that the promoter region of JMJD1C gene has POU5F1/OCT-4 binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, KDM3B suppressed differentiation of leukaemia cells, and was up-regulated in acute lymphoblastic leukaemia (ALL) patients. KDM3B might therefore play a key role in leukaemogenesis, although more studies are needed to support this preliminary hypothesis (86). Another statistical study conducted in breast cancer reported that overexpression of KDM3B/KDM5A and KDM6A is associated with improved and poor prognosis, respectively.…”
Section: Phd Finger (Phf) and Zinc Finger (Zf) Protein Familymentioning
confidence: 96%
“…Another statistical study conducted in breast cancer reported that overexpression of KDM3B/KDM5A and KDM6A is associated with improved and poor prognosis, respectively. Although these finding require further investigation, they suggest that rebalancing protein methylation levels might represent a new avenue for cancer therapy (86). JMJD1C has been proposed as an AR co-activator (87).…”
Section: Phd Finger (Phf) and Zinc Finger (Zf) Protein Familymentioning
confidence: 99%